Compliance to Health Protocols in the Implementation of the 2020 Regional Elections - Rizaldi Parani; Samuel Aditya; Liza Diniarizky Putri; Abdul Malik (Journal of Governance, 2021)
The regional elections (Pilkada) of 2020 have been concluded, and could be considered a success. Yet, its implementation cannot be said to be entirely successful, considering the lack of concern of political parties in helping the Government handle the Covid-19 pandemic through their political campaigns.  This study intends to discuss political communication carried out by political parties in an effort to raise awareness of preventing the spread of Covid-19 to the public during the 2020 Pilkada in Indonesia. The approach taken is qualitative, collecting data through in-depth interviews, with the subjects comprising of representatives of political parties and political communication experts.  The study finds that the bulk of the political campaigns carried out by political parties is focused on winning the elections, rather than on efforts to help deal with Covid-19. Community involvement also tends to be low in the 2020 elections, due to a lack of understanding of digital literacy and reluctance to vote due to a lack of understanding of health protocols.Keywords: health protocols; regional elections; community involvement.